LINTASAN PEMIKIRAN ESTETIKA PUISI INDONESIA MODERN (THE PERIOD OF ORIENTATION MINDED INDONESIAN’S MODERN POETRY AESTHETIC) - Heri Suwignyo (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2013)
AbstractThe Period of orientation minded Indonesian’s modern poetry aesthetic. The orientationminded Indonesian’s modern poetry aesthetic leads to aesthetic theory of harmony,deviation, and emancipatory. The conception of poetry by Sanusi Pane, Rustam Effendi’spoems appearance, and the sonnets by M. Yamin which have soul about nationalism,have relation to harmony of pantun and syair’s asthetic. Mind of deviation aestheticmarked by Chairil’s free poetry that emphasized the depth of the meaning rather thanlinguistic devices. Emancipatory aesthetic found by credo Sutardji that liberating wordsfrom the hegemony of meaning. Remy Silado offering the mbeling poem’s aesthetic asan integral part of the aesthetics of Indonesian’s contemporary poetry. Those minded isvery useful for the construction of the historiography Indonesian’s modern poetryaesthetic which is until right now still through emptyness.Keywords: indonesian poetry aesthetics, aesthetic harmony, aesthetic deviation,aesthetic emancipatoryAbstrakLintasan Pemikiran Estetika Puisi Indonesia Modern. Orientasi pemikiran estetika puisiIndonesia modern mengarah pada teori estetika harmoni, deviasi, dan emansipatori.Konsepsi sajak oleh Sanusi Pane, penampilan sajak-sajak Rustam Effendi, dan sonetasonetayang berjiwa kebangsaan M. Yamin secara harmoni masih terikat pada estetikapantun dan syair. Pemikiran estetika deviasi ditandai oleh kemunculan puisi-puisibebas Chairil yang menekankan pada kedalaman makna daripada sarana kebahasaan.Pemikiran estetika emansipatori ditemukan pada kredo Sutardji yang membebaskankata dari penjajahan makna. Remy Silado menawarkan estetika puisi mbeling sebagaibagian integral dari estetika puisi Indonesia kontemporer. Itu semua sangat bergunauntuk penyusunan historiografi estetika puisi Indonesia modern yang hingga saat inimasih mengalami kekosongan.Kata-kata kunci: estetika puisi Indonesia, estetika harmoni, estetika deviasi,estetika emansipatori